The relationship of students’ prior knowledge and emotional intelligence to mathematical connection ability - Muhammad Daut Siagian; Suwanto Suwanto; Rosliana Siregar (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2021)
Students should have a good mathematical connection ability to support their learning success. Many factors affect the mathematical connection ability, including prior knowledge and emotional intelligence. This study aimed to describe the simultaneous and partial effect of students’ prior knowledge and emotional intelligence on mathematical connection ability. This study involved 34 ninth graders of one of the public junior high schools in Lembang Regency, Indonesia, as the sample. The data was collected using a test consisting of a prior knowledge test and a mathematical connection ability test on the circle topic, and a questionnaire to measure students’ emotional intelligence. We analyzed the collected data by descriptive statistics, multiple regression, and partial correlation. The results revealed that the prior knowledge and emotional intelligence together had a significant effect on mathematical connection ability, with a contribution of 23.6%. In addition, there was a significant positive effect between prior knowledge and mathematical connection ability with a contribution of 75.1% and a significant positive effect between emotional intelligence and mathematical connection ability with a contribution of 12.2%.